Management of Chest Trauma in Bangladesh Perspective: Experience of a Decade (Cardiovascular Journal, 2019)
Background: Thoracic trauma is one of the leading causes of morbidity and mortality in developing countries. In this study, we present our 10-year experience in the management and clinical outcome of 437 chest trauma cases as a result of blunt and penetrating injuries in two medical college hospitals of Bangladesh.Methods: We reviewed 437 cases of chest trauma between January 2006 and December 2015.The mean age of our patients was 33 ± 15 years mostly males with blunt injuries. Patients were evaluated and compared according to age, sex, etiology of trauma, thoracic and extra-thoracic injuries, complications, and mortality.Results: The leading cause of the trauma was road traffic accident (61%) followed by violence (23%). Hemothorax (62%), Pneumothorax (51%), rib fractures (38%), and lung contusion (35%) were the most common types of injury. Associated injuries were documented in 35% of patients (extremities 18%, abdomen 12%, head 5%). Minority of the patients required thoracotomy (6%), and tube thoracostomy (56%) was sufficient to manage the majority of cases. Mean hospital stay was 5.5 ± 4.8 days. The overall mortality rate was 3.6%.Conclusion: Road traffic accident was the most common cause of chest trauma rather than violence in this series, this necessitates epidemiologic or multi-institutional studies to know what are the causes of RTA contributes to chest trauma in Bangladesh. The number of fractured ribs can be used as simple indicator of the severity of trauma.Cardiovasc. j. 2019; 12(1): 3-8